Cooperativas de reciclagem na capital paulista: um estudo multicasos sobre a inclusão socioeconômica dos catadores de material reciclável - Peçanha, Reynaldo Schirmer (2015)
This study aimed to verify if the recycling cooperatives implant the collectors of recyclable material, socioeconomically or not. The research was based on bibliographical and documentary review on the subject and also the comparative analysis of multi-case study in three recycling cooperatives located in São Paulo. We used to collect data from semi-structured interviews with cooperative members of these organizations and direct non-participant observation. The chosen approach was the analysis of qualitative data with the support of Atlas.ti software. The results will offer suggestions with proposals to managers, companies and policy makers so that the socio-economic inclusion is more effective. The main results of the study showed that the inclusion of collectors of recyclable material is processed with greater emphasis by the economic dimension in which the generation of employment and income become important factors to promote citizenship of these workers. It was observed in the cooperatives eager, but little effectiveness in implementing programs aimed at the social dimension as inclusion factor, in which the categories 'education' and 'health' could have priority in their management. It's worth mentioning that the analyzed recycling cooperatives comply with their proposals to provide access to work and therefore income. However, gaps in the social dimension could be minimized by the most action of public authorities and companies, in partnership with these collective social enterprises, in drafting of strategic plans that seek to actions aimed at increasing access to health and education programs and professional training of collectors